Separate structural elements within internal transcribed spacer 1 of Saccharomyces cerevisiae precursor ribosomal RNA direct the formation of 17S and 26S rRNA. - van Nues, R W (1994)
Structural features of Internal Transcribed Spacer 1 (ITS1) that direct its removal from Saccharomyces cerevisiae pre-rRNA during processing were identified by an initial phylogenetic approach followed by in vivo mutational analysis of specific structural elements. We found that S. cerevisiae ITS1 can functionally be replaced by the corresponding regions from the yeasts Torulaspora delbrueckii, Kluyveromyces lactis and Hansenula wingei, indicating that structural elements required in cis for processing are evolutionarily conserved. Despite large differences in size, all ITS1 regions conform to the secondary structure proposed by Yeh et al. [Biochemistry 29 (1990) 5911-5918], showing five domains (I-V; 5'-->3') of which three harbour an evolutionarily highly conserved element. Removal of most of domain II, including its highly conserved element, did not affect processing. In contrast, highly conserved nucleotides directly downstream of processing site A2 in domain III play a major role in production of 17S, but not 26S rRNA. Domain IV and V are dispensable for 17S rRNA formation although an alternative, albeit inefficient, processing route to mature 17S rRNA may be mediated by a conserved region in domain IV. Each of these two domains is individually sufficient for efficient production of 26S rRNA, suggesting two independent processing pathways. We conclude that ITS1 is organized into two functionally and structurally distinct halves.